Implementasi Algoritme Profile Matching dan Pengujian UAT Untuk Memilih Karyawan Terbaik - Siswanto Siswanto; Recky Juniansyah Asad; Gunawan Pria Utama; Wahyu Pramusinto; M Anif (Ikatan Ahli Informatika Indonesia, 2020)
In supporting the performance or enthusiasm of employees in the regulation department, the company gives rewards or awards to employees who get the title as the best employees in the form of money with a certain nominal value. It is expected that this reward can stimulate the enthusiasm of employees at work. But when assessing employees there are obstacles, including subjective judgments and calculation errors often occur in determining who the employee gets the title of the best employee. The application for selecting the best employees has been made using the profile matching algorithm. In this study using two aspects, namely aspects of performance consisting of speed of work, quality of work, work responsibilities and problem solving and personality aspects consisting of absenteeism, work knowledge, attitude, team work and loyalty. So that the final results of this study in the form of the results of the testing process with the UAT, the respondents agreed (above 91.2%) that overall the application for selecting employees helps the decision maker management in providing the best employee recommendations based on ranking correctly.